2014
DOI: 10.1161/01.str.0000442009.06663.48
|View full text |Cite|
|
Sign up to set email alerts
|

Guidelines for the Prevention of Stroke in Women

Abstract: 1545Purpose-The aim of this statement is to summarize data on stroke risk factors that are unique to and more common in women than men and to expand on the data provided in prior stroke guidelines and cardiovascular prevention guidelines for women. This guideline focuses on the risk factors unique to women, such as reproductive factors, and those that are more common in women, including migraine with aura, obesity, metabolic syndrome, and atrial fibrillation. Results-We provide current evidence, research gaps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
414
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 774 publications
(441 citation statements)
references
References 501 publications
5
414
0
13
Order By: Relevance
“…The importance of sex‐specific risk assessment in primary stroke prevention is emphasized in both the 2014 American Heart Association/American Stroke Association primary prevention guidelines,55 and those specific to women 20. The relevance of sex‐specific risk in primary prevention is supported by our observation that sex was included in 69% of the population sample–stroke models.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The importance of sex‐specific risk assessment in primary stroke prevention is emphasized in both the 2014 American Heart Association/American Stroke Association primary prevention guidelines,55 and those specific to women 20. The relevance of sex‐specific risk in primary prevention is supported by our observation that sex was included in 69% of the population sample–stroke models.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, our finding that all 4 models estimate lower risk of death after ischemic stroke for women than otherwise similar men was surprising given the inconsistency of the literature, which has frequently reported worse prognoses in women (particularly in populations untreated with thrombolysis) 17, 68, 69, 70. Finally, it is notable that about half of the models predicting stroke in a population sample were sex stratified (thereby allowing the effects of risk factors to vary among men and women), in keeping with evidence that sex modifies the effect of some risk factors on stroke risk 20, 71…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In review of 55 observational studies using the newer hormonal contraception, which now has lower estradiol levels, there was a trend towards increased risk of thromboembolic events but it did not reach statistical significance. However, it was noteworthy that the hormone that seemed responsible for the higher number of events was progestin [5][6][7][8][9]. There have been no reports that Implanon® increases risk of stroke, however, it does contain progestin so manufacturer's packing insert notes that it could be associated with increased risk in high risk patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Aging is the most important nonmodifiable risk factor for stroke, and aged patients exhibit impaired stroke recovery. [4] Consistent with clinical data, findings from animal models have demonstrated that aged mice have higher mortality and worse outcomes when subjected to same duration of occlusion compared with young mice, yet paradoxically, the infarct damage is smaller in the aged mice.…”
Section: Introductionmentioning
confidence: 99%